Eficiência energética das tipologias representativas de edifícios residenciais de um bairro à luz do PBE Edifica - Giacomin, Regiane Faria (2017)
The energy consumption in Brazil in the last 10 years shows a significant increase, and currently about 54% of Brazilian electricity consumption corresponds to the residential, commercial, public and service sectors. In this way, it is important to formulate strategies that promote the energy efficiency on buildings, and it is necessary to understand their thermal and energy performance. Technical regulations were developed by Brazilian buildings Labeling Program, PBE Edifica, to classify the level of energy efficiency of buildings. Thus, identifying the existence of a gap in Vitória, ES, about knowing the level of energy efficiency of its buildings, the objective of this research was to define the energy efficiency level of the multifamily residential buildings in Jardim Camburi, a neighborhood in the capital of Espírito Santo, southeast of Brazil , according to the PBE Edifica, and through representative buildings. To do so, this research selected four representatives buildings based on the analysis of the most frequent typologies that represent the multifamily residential buildings of the neighborhood. 663 buildings were mapped and classified. The representative buildings were evaluated for their energy efficiency in relation to Energy Labeling, RTQ-R, PBE Edifica technical regulation. The results of the housing units (UH) were analyzed for degrees-hour for cooling, relative consumption for refrigeration, envelope for summer and final classification of the UH with water heating system and analyzed the results of multifamily construction. Thus, considering the analysis of the results of representative buildings and ZB 8, it was identified that the main architectural variables are solar protection device, solar water heating system and thermal absorption. Thus, these results provide data that contribute to an efficient policy for the housing industry and city, as well as allowing studies on the incorporation of measures that promote energy efficiency in the sector.